2016
DOI: 10.18697/ajfand.73.16190
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Vitamin a Deficiency Among Infants in Western Kenya Using a Cross-Sectional Analysis

Abstract: Vitamin A (VA) deficiency (VAD) is a major nutritional public health problem among children under-5-years-old in the developing world including Kenya. A community-based crosssectional survey among 1,630 children (aged 6-23 mos) was undertaken in Western Kenya. A questionnaire was administered to collect demographic, socio-economic and dietary intake information. Prevalence of low retinol-binding protein (RBP) concentrations was assessed using Dried Blood Spot (DBS) methodology. Analysis of RBP was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…This becomes an exacerbating factor to increased prevalence of Vitamin AD eficiency [VAD] considering that Western Kenya has the lowest Vitamin A Supplementation [VAS] coverage at 19.8% compared to 30.3% nationally [11]. [23] in three counties (Busia, Vihiga and Bungoma) in Western Kenya showed that despite the high prevalence of VAD in the area, most of pre-natal and post-natal mothers were not aware about VAD, VAS and the importance of consumption of vitamin A rich foods in their household diets.…”
Section: Food Consumption Per Food Groupsmentioning
confidence: 99%
“…This becomes an exacerbating factor to increased prevalence of Vitamin AD eficiency [VAD] considering that Western Kenya has the lowest Vitamin A Supplementation [VAS] coverage at 19.8% compared to 30.3% nationally [11]. [23] in three counties (Busia, Vihiga and Bungoma) in Western Kenya showed that despite the high prevalence of VAD in the area, most of pre-natal and post-natal mothers were not aware about VAD, VAS and the importance of consumption of vitamin A rich foods in their household diets.…”
Section: Food Consumption Per Food Groupsmentioning
confidence: 99%
“…The levels of vitamins A and C from one medium-sized papaya (whose edible portion is about 350 g) exceed the Dietary Reference Intakes of 3000 IU for vitamin A and 90 mg for vitamin C, as established by the United States Food and Nutrition Board for adult minimum daily requirements (Ming et al, 2008). Consumption of this fruit is important in preventing vitamin A deficiency, a cause of childhood blindness in many developing countries, including Kenya (Oyunga et al, 2016). The fruit is reasonably priced and is rich in nutrients, making it a "common man's" fruit.…”
Section: Introductionmentioning
confidence: 99%
“…For example, polarized narratives in research addressing the intersecting goals of food security and biodiversity conservation are driven by the underpinning conceptualization of the problem as either technical or socio-political (Loos et al 2014 ; Glamann et al 2015 ). Similarly, the narrative explaining food insecurity as a result of insufficient production and population growth contrasts with explanations based on unequal distribution of social power as well as economic and physical resources (Sen 1981 ; Legwegoh and Fraser 2015 ). In the agricultural biosciences, calls for gene patenting, corporate funding of public institutions and public–private partnerships conflict with arguments that seeds should be regarded as public goods (Scoones 2002 ; Stone 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the narrative explaining food insecurity as a result of insufficient production and population growth contrasts with explanations based on unequal distribution of social power as well as economic and physical resources (Sen 1981 ; Legwegoh and Fraser 2015 ). In the agricultural biosciences, calls for gene patenting, corporate funding of public institutions and public–private partnerships conflict with arguments that seeds should be regarded as public goods (Scoones 2002 ; Stone 2015 ). Such polarization presents serious challenges for sustainability science, not simply in terms of conflicting policy prescriptions, but also in the perceived legitimacy of the science itself (Bäckstrand 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation